Cleaner Production towards a sustainable transition. (20th January 2017) - Almeida, C.M.V.B.; Agostinho, F.; Huisingh, D.; Giannetti, B.F.
Abstract: This special volume of the Journal of Cleaner Production was built principally upon articles submitted for the 5th International Workshop Advances in Cleaner Production held in São Paulo, Brazil, in 2015. The43 articles emphasize the imperative need for shifting from unsustainable production and societal patterns to sustainable ones. They provide many new technological and/or management related approaches to help industries, governments, and society to speed up the transition to sustainable patterns. Efforts on defining and solving problems with the special accent upon a sustainable solution for the use of raw materials and energy, technological advances, product and policy changes are presented and deeply discussed. Improved corporate management for sustainable societal transitions is discussed, highlighting consumer empowerment in sponsoring implementation of innovative cleaner technologies within companies, industrial sectors, supply chains and countries. Multiple examples are provided relating the successful combination of cleaner production in policy structures, illustrating on how the focused work in production sectors is delivering multiplier benefits and creating conditions to facilitate a "leapfrogged" path toward SD.